THE BENEFIT OF USING SMART MANUFACTURING WITH ANALYSIS OF DIGITAL PRODUCT DEVELOPMENT: A REVIEW - Mareta Ramadhanis Suherman (Universitas Sriwijaya, 2020)
Application product development and manufacturing using computer-aided technologies and what has already been implemented successfully in some segments of large-scale industry and suppliers. This study aimed to established a general understanding of the development of digital product development and manufacturing. The method of this study is a review of smart manufacturability analysis for digital product development. This study described product development is supported by CAD CAM and CAE programs from design and development with Cloud-Based Design with Manufacturing (CBDM). The results from this journal review are to know the factors that influence the results of 3D printing and how to fix these problems. The problem is by using cloud base there are still problems when translating digital forms into physical forms in the form of STL. or obj in this case using FDM (Fused Deposition Modeling). can be improved by using 3D SLA printer technology because SLA (Stereolithography) can produce good print results and complicated designs